2022
DOI: 10.1038/s41598-022-13828-4
|View full text |Cite
|
Sign up to set email alerts
|

Anti-dermatophytic activity of cold atmospheric plasma against Trichophyton rubrum via affecting fungal growth, morphology, drug susceptibility and HSP90 gene expression

Abstract: Trichophyton rubrum, a major human pathogenic dermatophyte, is responsible for the most recurrent dermatophytoses as globally important superficial fungal infections. Typical chemotherapy is used to handle such infections; however, emerging drug resistance and side effects necessitate the new remedial method development. Cold atmospheric plasma (CAP) is an emerging technology, consisted of neutral and charged particles and photons newly developed as a potent and safe antimicrobial technique to combat drug-resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…reported similar CAP‐induced cell wall damage in T. rubrum under scanning electron microscopy. 17 Traditionally, studies evaluating the effect of CAP in Malassezia genus have focused on planktonic cells in pure culture despite the fact that most microbes exist as organized biofilm communities of cells in natural ecosystems. The biofilm structure enhances the inherent resistance of microbes to both physical and chemical stressors and mediates the regulation of community‐driven gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported similar CAP‐induced cell wall damage in T. rubrum under scanning electron microscopy. 17 Traditionally, studies evaluating the effect of CAP in Malassezia genus have focused on planktonic cells in pure culture despite the fact that most microbes exist as organized biofilm communities of cells in natural ecosystems. The biofilm structure enhances the inherent resistance of microbes to both physical and chemical stressors and mediates the regulation of community‐driven gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our results, Safi-Samghabadi et al reported similar CAP-induced cell wall damage in T. rubrum under scanning electron microscopy. 17 Traditionally, studies evaluating the effect of CAP in Malassezia genus have focused on planktonic cells in pure culture despite the fact that most microbes exist as organized biofilm communities of cells in natural ecosystems.…”
Section: Discussionmentioning
confidence: 99%